The Role of Physical Education in Building Students' Self-Confidence - Luky Sofiana Zebua; Gita Febria Friskawati; Diky Hadyansah (Journal of Physical and Outdoor Education, 2026)
Previous research shows differences in contexts, teaching approaches and characteristics that influence research outcomes. Therefore, it is necessary to review the literature that identifies, analyzes and identifies findings from previous research. Physical education is expected to be a means of increasing physical activity, movement skills, health, and building confident character. This research uses the literature review method by analyzing various related articles. The results of the analysis show that students' self-confidence grows through; (1) a participatory and meaningful pedagogical approach; (2) a supportive learning environment; (3) students' movement competence, and (4) motivation to develop physically and psychologically. Interesting and relevant teacher behavior also influences the character building process. Pedagogical and social approaches can make students more confident, focused and comfortable in expressing themselves. Imitation of behavior requires physical abilities and motor skills, which if developed will increase students' confidence and active participation. In addition, learning motivation is an important factor in encouraging students to build confidence through physical education